Emotional Regulation Following Acquired Brain Injury: Associations With Executive Functioning in Daily Life and Symptoms of Anxiety and Depression - Stubberud, Jan; Løvstad, Marianne; Solbakk, Anne-Kristin; Schanke, Anne-Kristine; Tornås, Sveinung (Frontiers in Neurology, 2020)
Objective. To examine whether a questionnaire measuring emotional regulation after acquired brain injury adds clinical information beyond what can be obtained with a comprehensive executive function questionnaire and an anxiety and depression measure. Method. Seventy adult persons (age 19-66 years, M = 43, SD = 13) with acquired brain injury in the chronic phase and executive function complaints. All were recruited to participate in a randomized controlled trial (NCT02692352) evaluating the effects of cognitive rehabilitation. Traumatic brain injury was the dominant cause of injury (64%), and mean time since injury was 8 years. Emotional regulation was assessed with the Brain Injury Trust Regulation of Emotions Questionnaire (BREQ). Executive function was assessed with the Behavior Rating Inventory of Executive Function Adult Version (BRIEF-A). The Hopkins Symptom Checklist 25 (HCSL-25) was employed to measure anxiety and depression symptoms. Results. Overall, significant correlations were found between reports of emotional regulation (BREQ) and executive function in daily life (BRIEF-A). Furthermore, our analyses revealed a significant relationship between self-reported scores of emotional regulation (BREQ) and symptoms of anxiety and depression (HSCL-25). Conclusion. The significant associations between the BREQ and most of the other clinical measures indicate that, for patients with acquired brain injury, the BREQ does not add substantial information beyond what can be assessed with the BRIEF-A and the HSCL-25.